Ovarian thrombosis and uterine synechiae after arterial embolization for a late postpartum haemorrhage - Françoise Vendittelli; Denis Savary; Brigitte Storme; Virginie Rieu; Pascal Chabrot; Cécile Charpy; Didier Lémery; Bernard Jacquetin (Elsevier, 2015)
Background: We report two unusual separate complications after uterine artery embolization for a late postpartum haemorrhage. This report appeared important to us in view of the apparent absence of any other publications on this topic. Case presentation: We report the case of a 25-year-old woman, gravida 3, para 1, admitted for uterine bleeding 7 days after a spontaneous delivery at term, in our university hospital. A suction curettage and then, after persistent bleeding, uterine artery embolization were necessary. Immediately after the embolization, a bilateral ovarian thrombosis occurred, subsequently followed by amenorrhea, due to uterine synechiae, and depression. Hysteroscopic surgery was performed to remove the adhesions. A complete work-up for thrombophilia showed a heterozygous mutation of the factor V gene R506Q. The pathology examination found subinvolution of the placental bed. One month after treatment of the synechiae (and insertion of a copper IUD for contraception), the woman's menstrual cycle returned to normal. Her clinical examination 19 months later was normal. Conclusions: This case teaches us that one rare complication can hide another! It is important to consider the diagnosis of subinvolution of the placental bed in cases of late PPH and to know the complications associated with vascular artery embolization in order to provide the most rapid and least invasive treatment.